Case Study: New Approaches to Leadership: Planning and Delivery of a MA/MBA Social Work Programme. Issue 1 (1st January 2023) - Allain, Lucille; Hingley-Jones, Helen; Hartog, Mary; Haddock-Millar, Julie
Abstract : This case study discusses the development and delivery of a MA/MBA social work leadership programme which was part of a range of new learning opportunities in a social work teaching partnership. Following the mapping of workforce needs across the employers, a key theme emerged in relation to the need for a leadership programme for managers. This case study brings together the process of developing and delivering new leadership programmes and includes student feedback and an overview of the pedagogic principles underpinning our approach. An explanation is given about how this facilitated the building of communities of practice across partnership employers and academic departments.